The Experiences of Parents of and Students With Visual Impairments With 4to24, a Transition Application. (September 2022) - Steverson, Anne; Cmar, Jennifer L.; Antonelli, Karla
Introduction: This article describes the field test of 4to24, a transition application (app) for parents of and students with visual impairments. In this stage of the development process, researchers evaluated the app's usability and gained feedback on app use and experience from end users.Methods: Participants, including 27 parents of and 19 students with visual impairments, used 4to24 for 6 months. They completed a baseline survey, a survey about the account setup process, and three additional surveys at 2-month intervals (i.e., 2, 4, and 6 months).Results: Participants found the app account setup process quick and easy to complete. Parents and students used the app more frequently during the first 2 months, and then app usage decreased over time. Participants' average ratings for app enjoyability, ease of use, understandability of information, and relevance of information were generally high and consistent across time points. Participants found 4to24 useful to track activities to help students prepare for college and work, and most planned to continue using it after the study.Discussion: Findings indicate that the app was usable, enjoyable, easy to use, and helpful. The decline in app usage over the 6 months may signify that participants lost interest, were impacted by the COVID-19 pandemic, or spent more time working on activities within the modules. Students rated app enjoyability and relevance higher than parents, which may relate to the language and tone of the student-focused modules. Introductory topics may have been unnecessary for some parents, which could have contributed to their lower relevance ratings.Implications for Practitioners: Service providers can inform parents and students about 4to24 and its potential benefits. 4to24 can encourage conversations about college and work, provide resources and activity suggestions, and serve as a resource for parents who are not connected or knowledgeable about services.